A Novel Time-Dependent CENP-E Inhibitor with Potent Antitumor Activity - Ohashi, Akihiro; Ohori, Momoko; Iwai, Kenichi; Nambu, Tadahiro; Miyamoto, Maki; Kawamoto, Tomohiro; Okaniwa, Masanori (PLOS ONE, 2015)
Centromere-associated protein E (CENP-E) regulates both chromosome congression and the spindle assembly checkpoint (SAC) during mitosis. The loss of CENP-E function causes chromosome misalignment, leading to SAC activation and apoptosis during prolonged mitotic arrest. Here, we describe the biological and antiproliferative activities of a novel small-molecule inhibitor of CENP-E, Compound-A (Cmpd-A). Cmpd-A inhibits the ATPase activity of the CENP-E motor domain, acting as a time-dependent inhibitor with an ATP-competitive-like behavior. Cmpd-A causes chromosome misalignment on the metaphase plate, leading to prolonged mitotic arrest. Treatment with Cmpd-A induces antiproliferation in multiple cancer cell lines. Furthermore, Cmpd-A exhibits antitumor activity in a nude mouse xenograft model, and this antitumor activity is accompanied by the elevation of phosphohistone H3 levels in tumors. These findings demonstrate the potency of the CENP-E inhibitor Cmpd-A and its potential as an anticancer therapeutic agent.